Cannabis indica as a motivation for foreign travel by Polish citizens - Matczak, Andrzej; Pawlicki, Przemysław (Turyzm/Tourism, 2016)
Based on an anonymous on-line questionnaire survey, conducted among 1000 respondents, the authors present their demographic, socio-economic and spatial profile, their attitude to cannabis and the tourist trips they went on (scale, directions, destinations), involving cannabis consumption. Tourist trips of this kind were attractive to quite a large number of young people, mostly inhabiting large Polish cities, who usually had used and continued to use this drug. Trips inspired by cannabis were most often made to the nearby Czech Republic and Netherlands, as well as (less frequently) to Spain.